PENGARUH PARTISIPASI MASYARAKAT DAN TRANSPARANSI KEBIJAKAN PUBLIK TERHADAP HUBUNGAN ANTARA PENGETAHUAN DEWAN TENTANG ANGGARAN DENGAN PENGAWASAN KEUANGAN DAERAH - Anwar, Saiful; Sari, dan Rida Perwita (Journal of Accounting and Strategic Finance, 2009)
Many studies about budget behavior have been primarily conducted in private organization but rarely in public organization. This studi examined influence of public participation and public policy transparancy on the relationship between budgeting knowledge and budgeting control. The studi sample was drawn from Kota Sidoarjo. Fourteen legislative participated in this study. Hypothesis are tested empirically used regression. The result of study indicated that, first, budgeting knowledge aren’t statically significant, positive coeficient indicated that high budgeting  knowledge so high budgeting control, second, interaction between public participation with budgeting knowledge aren’t statically significant, thrid, interaction public policy transparancy between with budgeting knowledge aren”t statically significant. Keywords: Public Participation, Transparancy Public Policy, Budgeting Knowledge, Budgeting Control (APBD)